Criminal cases review commission: legal aid and legal representatives, 2019-2021 - Vogler, Richard (UK Data Service, 2022)
The dataset includes a set of transcripts of interviews with legal practitioners (Legal Executives, Solicitors, Barristers) who were involved in assisting applicants to the Criminal Law Cases Commission. Because of the Covid 19 pandemic some of the interviews were conducted remotely. The interviewees were asked to discuss the impact on their work and on their clients, of successive cuts in legal aid provision during the period 2014-2021. Since 1997 the CCRC has been the only independent reviewer of potential miscarriages of justice. It is an institution of crucial importance in the criminal justice process, as it acts to scrutinise the decisions, and decision making processes, of our criminal courts. Its ability to independently scrutinise such decisions increases legitimacy, accuracy and public confidence in the criminal justice system. However, the data held by the CCRC is difficult to access, requiring the consent and co-operation of the department, and the Ministry of Justice. Data held by the CCRC, coupled with data available from lawyers who prepare applications for review and cases on behalf of clients, offers a unique insight into how the CCRC has been affected by austerity measures initiated by recent governments. The CCRC reports directly to the Justice Select Committee, and raised concerns about the impact of legal aid cuts as part of those reports. In 2016, the Justice Select Committee agreed that such matters should be investigated, and tasked the CCRC with commissioning independent research on this subject. The CCRC released an unfunded call for suitably qualified researchers to examine the impact of funding cuts in early 2016, and the project team successfully secured access to the CCRC's unique data set as a result of that competitive tender. The full research proposal was agreed in spring 2017. This is particularly timely in light of the government's announcement (in early 2017) to conduct a review of the Legal Aid, Sentencing and Punishment of Offenders Act 2012. Welsh has been involved in early discussions with Ministry of Justice policy advisers about that review. It is hoped that the reports produced by this study will provide the government, the CCRC and lawyers with access to important though rarely accessible material. Recent changes to legal aid policy have affected the levels of representation available to defendants who seek case review with the CCRC. The policy changes that the Justice Select Committee is most interested in are changes in the funding scheme brought about by the Legal Aid Sentencing and Punishment of Offenders Act 2012, the coming into force of reduced expert fees under the Criminal Legal Aid (Remuneration) Regulations 2013 and the 8.75% fee cut introduced in March 2014. The overarching theme of the project is, therefore, the impact of legal aid cuts on applications made to the CCRC, which influences the way that the institutions of criminal justice operate and, therefore, influences the interests of civil society. We use both qualitative and quantitative methods to examine pre-existing data held by the CCRC, and to create data about how the changes detailed above have influenced lawyer behaviour. We use that data to examine fluctuations in the volume of applications received by the CCRC, and on the quality of applications that are being received. We examine whether it is possible to identify trends in the number of applications being submitted; whether such trends reflect changes in legal aid provision; and whether it is possible to detect a change in the quality of the preparation of applications which are submitted.The research will inform policy developments in access to justice, and will provide the CCRC with guidance about their processes so that they are able to operate in the most effective and efficient way for applicants. It will also add to a growing body of literature on access to justice, will provide lawyers with information that will enable them to ensure they are operating as effectively as possible for their clients and will inform applicants and their families about the way that legal aid operates when making applications to the CCRC.